Dances With 'Religion': A Critical History of the Strategic Uses of the Category of Religion by the Government of Canada and First Nations, 1885 to 1951 - Ruecker, Michael (Université d'Ottawa / University of Ottawa, 2015)
This thesis examines the historical record of the late 19th and early 20th century Canadian law against indigenous ceremonies, such as the potlatch and the sun dance, in order to investigate whether an alternative narrative of this history is possible. The main source of data is the archive of the Department of Indian Affairs, containing all the official correspondence that the department sent and received regarding these ceremonies during the time that the law was in effect. Classifying these practices as religious ceremonies, I will argue, was not an obvious or necessary classification, but a strategic move that was beneficial in the short term, both for First Nations advocates of the ceremonies and for their federal government opponents. This research sheds light on the political relationships between Canada and its First Nations, as well as clarifying the ways in which 'religion' is a strategic, rather than an absolute, category.
Keywords: Canada; First Nations; Theory of Religion